Comparing one-stage and two-stage treatment approach of cholelithiasis and choledocholithiasis (Annals of Medical Research, 2021)
None
Keywords: Endoscopic Retrograde Cholangio Pancreatography; Laparoscopic; Interval cholecystectomy.